Complementary Romanovski–Routh Polynomials, Orthogonal Polynomials on the Unit Circle, and Extended Coulomb Wave Functions - Martínez-Finkelshtein, A.; Silva Ribeiro, L. L. [UNESP]; Sri Ranga, A. [UNESP]; Tyaglov, M. (Springer Nature, 2020)
In a recent paper (Martínez-Finkelshtein et al. in Proc Am Math Soc 147:2625–2640, 2019) some interesting results were obtained concerning complementary Romanovski–Routh polynomials, a class of orthogonal polynomials on the unit circle and extended regular Coulomb wave functions. The class of orthogonal polynomials here are generalization of the class of circular Jacobi polynomials. In the present paper, in addition to looking at some further properties of the complementary Romanovski–Routh polynomials and associated orthogonal polynomials on the unit circle, behaviour of the zeros of these extended Coulomb wave functions are also studied.
Keywords: orthogonal polynomials on the unit circle; para-orthogonal polynomials; Romanovski–Routh polynomials; second order differential equations